Fabrication of a SnO2–Sb electrode with TiO2 nanotube array as the middle layer for efficient electrochemical oxidation of amaranth dye. (June 2023) - Chen, Daying; Zhao, Lin; Chen, Danning; Hou, Pengfei; Liu, Jiashu; Wang, Chuanbin; Aborisade, Moses Akintayo; Yin, Meilin; Yang, Yongkui
Abstract: Efficient, stable, and easily producible electrodes are useful for treating dye wastewater through electrochemical oxidation. In this study, an Sb-doped SnO2 electrode with TiO2 nanotubes as the middle layer (TiO2 -NTs/SnO2 –Sb) was prepared through an optimized electrodeposition process. Analyses of the coating morphology, crystal structure, chemical state, and electrochemical properties revealed that tightly packed TiO2 clusters provided a larger surface area and more contact points, which is conducive to reinforcing the binding of SnO2 –Sb coatings. Compared with a Ti/SnO2 –Sb electrode without a TiO2 -NT interlayer, the catalytic activity and stability of the TiO2 -NTs/SnO2 –Sb electrode significantly improved ( P   <  0.05), as reflected by the 21.8% increase in the amaranth dye decolorization efficiency and 200% increase in the service life. The effects of current density, pH, electrolyte concentration, initial amaranth concentration, and the interaction between various combinations of parameters on the electrolysis performance were investigated. Based on response surface optimization, the maximum decolorization efficiency of the amaranth dye could reach 96.2% within 120 min under the following set of optimized parameter values: 50 mg L −1 amaranth concentration, 20 mA cm −2 current density, and 5.0 pH. A potential degradation mechanism of the amaranth dye was proposed based on the experimental results of a quenching test, ultraviolet–visible spectroscopy, and high-performance liquid chromatography-mass spectrometry. This study provides a more sustainable method for fabricating SnO2 –Sb electrodes with TiO2 -NT interlayers to treat refractory dye wastewater. Graphical abstract: Image 1 Highlights: A SnO2 –Sb electrode with TiO2 nanotube as the middle layer was fabricated. TiO2- NTs layer improves the catalytic activity and stability of electrode. Amaranth dye decolorization was optimized by response surface methodology. Ecological risks of amaranth intermediate metabolites cannot be ignored. Potential degradation mechanism and pathway of amaranth is proposed.